The Relationship of Social Capital With Job Satisfaction And The Quality of Nursing Care In Critical Care Nurses - Mohammad Ali Heidari Gorji; Fatemeh Naderifar; Ali Hesamzadeh; Nouraldin Moosavinasab; Ali Morad Heidari Gorji (Asia Pacific Journal of Health Management, 2023)
Introduction and Objective: Social capital is an important factor influencing job satisfaction and the quality of nursing care provided by nurses. This study aimed to examine the relationship between social capital, job satisfaction, and quality of nursing care among critical care nurses working in critical care wards (CCWs).